AUD719: Audit and investigation / Faculty of Accountancy - UiTM, Faculty of Accountancy (2018)
This course is designed to provide an overview of the development, implementation and current issues of auditing. It provides an understanding of the concepts and principles in auditing. Topics discussed include auditor’s responsibility, audit planning, control issues, assurance services and impact of technology in audit process. It also examines the audit practice and methodology within the statutory and regulatory requirements and behavioral aspects of auditing.